Analisis Sikap Peduli Lingkungan Siswa Berdasarkan Gender - Hafiza, Auramia; Ferry, Dharma (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Environmental concern is crucial for understanding individual and societal behaviors related to environmental preservation. Environmental concern is a key factor influencing pro-environmental behaviors, such as sustainable resource usage and support for environmental policies. This study aimed to understand the differences in environmental concerns between male and female students at MAN 1 Kabupaten Kerinci. The research method was a survey with a quantitative approach involving 122 students from grades XI and XII. The research instrument consisted of a questionnaire on environmental concerns comprising 22 statements. The results of the analysis indicate significant differences in environmental concerns between genders. The proportion of female students concerned about the environment (86.9%) is substantially higher than that of male students (13.1%). The majority of respondents demonstrated high or very high levels of environmental concern. The data also reveal disparities in overall scores, with female students tending to score higher. Further analysis of attitude indicators shows that female students consistently exhibit higher levels of environmental concern than male students across all indicators. This study provides in-depth insights into the differences in environmental concerns based on gender at MAN 1 Kabupaten Kerinci.